Molecular and taxonomic characterisation of introduced specimens of Poecilia reticulata in the lower Paraguay River basin (Cyprinodontiformes: Poeciliidae) - Rosso,Juan J. (2017)
ABSTRACT Poeciliids comprise around 300 species inhabiting the fresh and brackish waters of the Americas and Africa. Poecilia reticulata is native to Northeastern South America and Trinidad and Tobago. In this paper, introduced specimens of P. reticulata collected in the lower Paraguay River in Argentina, were characterized by means of molecular and taxonomic approaches. We further explore, by means of DNA Barcoding, the singularity of the genetic identity of these specimens. Ocurrence of P. reticulata in the lower Paraguay River represents the first record of this species in Argentina. Thirteen individuals of P. reticulata were collected. DNA barcoding showed that all five specimens sampled belong to a single mitochondrial lineage, which was also present in 11 countries from five continents. The distance-based tree clearly grouped separetely four different clusters of P. reticulata when including public data. Genetic distance between the most divergent P. reticulata almost paralleled distance between this species and Poecilia mexicana and P. vivipara. Established populations from Paraguay could be one of the plausible sources for the introduced populations recorded in the lower Paraguay River. The presence of P. reticulata in an open waterway with known drainage to a natural stream is of major concern.